POLA ASUH ORANG TUA TERHADAP AKHLAK ANAK - Salis Irvan Fuadi; Nur Farida; Rindi Antika; Dwi Priharti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2020)
This research is motivated by problems in social life in the Karangreja Hamlet community, Dempel Village, namely the low quality of individual children's morals. This is due to the parenting style in which they partly become foreign and domestic workers. This study aims to determine the difference between the morals of children with the parenting of overseas workers' parents and parenting patterns of household parents in Karangrejo Hamlet, Dempel Village. This research uses a causal-comparative quantitative approach. For data collection techniques using questionnaires, interviews and documentation. As for the data analysis using t-test statistical analysis. From the results of the t-test analysis, it is known that there is a difference of 1,120 between the parenting patterns of parents of foreign and domestic workers towards the morals of children, with the value of ttable at N = 30, the significance level of 5% (95% confidence level) that is 2.045 tcount <t table or (1,120 <2,045) and at a significance level of 1% that is 2.756, then t <t table (1,120 <2,756). Provisions if tcount <ttable, the results are not significant. From the above analysis it can be concluded that the working hypothesis (Hi) is rejected, while the null hypothesis (Ho) is accepted.